Using the Box–Behnken Response Surface Method to Study Parametric Influence to Improve the Efficiency of Helical Gears - Huu Loc Nguyen (MDPI AG, 2021)
Studying gear power loss theoretically and determining the efficiency of a helical gear drive depend on many geometrical and working parameters, such as rotation speed, tooth number, gear ratio, helix angle, and torque, among others. In this paper, the Plackett–Burman screening design and the Box–Behnken response-surface method are used to consider how the above parameters influence gear drive efficiency, and experimental models are provided to evaluate these influences. The present results can be used to select the efficiency when calculating and designing gear transmissions and to choose the parameters for improving gear transmission efficiency.